ANALISIS HUBUNGAN BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DENGAN PENINGKATAN KINERJA PEGAWAI POLITEKNIK LP3I BANDUNG - Rahmat Ginanjar, Igus (POLITEKNIK LP3I JAKARTA, 2026)
Organizational culture is a system of values ​​and beliefs shared by people interacting within an organization, serving as a sense of identity and a guideline for behavior in achieving organizational goals. One factor in the success of organizational goals is leadership, particularly leadership style, which determines organizational performance, as evidenced by employee performance. The purpose of this study is to analyze the influence of organizational culture and transformational leadership style on improving employee performance. The study was conducted using a questionnaire survey of all employee respondents, aiming to gain a deeper understanding of social phenomena within a natural context. This study attempts to analyze organizational culture and leadership style on improving employee performance at the LP3I Bandung Polytechnic educational institution. This method was chosen because it captures the complexity of social reality comprehensively and contextually, and allows for deeper interpretation of the experiences and perspectives of informants to gain a deeper understanding of the phenomena under study, rather than generalizing the findings.